Efektivitas Penghambatan Ekstrak Daun Chaya (Cnidoscolus aconitifolius) terhadap Bakteri Vibrio harveyi - Aldiwa, Nurul Fitri; Basir, Buana; Mulyawan, Ardi Eko (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Vibrio harveyi bacteria are one of the main causes of mass mortality in shrimp in a short time. Chaya (Cnidoscolus aconitifolius) is a common plant that grows in many places in Central America, the Yucatan Peninsula of Mexico and has been widely cultivated in tropical and subtropical areas. The purpose of this study was to analyze the content of secondary metabolites in chaya leaves as antibacterials against Vibrio harveyi and to analyze the amount of inhibition of chaya leaves against Vibrio harveyi bacteria. The method used in this study was experimental with 4 treatments with 3 replications each, namely A (500 µg/mL chaya leaf extract) B (1000 µg/mL chaya leaf extract) C (Oxytetracycline antibiotic) and D (96% ethanol). The study was conducted from June to July 2024 at the Laboratory of Parasites and Fish Diseases, Faculty of Marine Sciences and Fisheries, Hasanuddin University. The results showed that the activity of chaya leaf extract (Cnidoscolus aconitifolius) did not show inhibition against V. harveyi bacteria at concentrations of 500 and 1000 µg/mL. Likewise, 96% ethanol did not show inhibition against V. harveyi bacteria. The inhibitory activity of Oxytetracyclin showed inhibitory activity with an average inhibition size of 9.26 mm. This is thought to be due to the low sensitivity of chaya leaf extract to V. harveyi bacteria. V. harveyi is known as a bacteria with a high level of malignancy when infecting, so it is thought to require a substance with stronger inhibitory activity.